Konsep Pendidikan Anak dalam Kitab Tarbiyatul Aulad Karya Sa’id Bin Ali Bin Wahf Al-Qahthani - Hanif, Muhammad; Fathurrohman, Mukhlis; Rochmawan, Alfian Eko (An-Nuha, 2025)
This study aims to examine the concept of child education according to Sa'id bin Ali bin Wahf Al-Qahthani in the book Tarbiyatul Aulad, its relevance to child education in the modern era, and the application of its principles in contemporary Islamic education practices. This study uses a qualitative method with a library research approach through primary and secondary literature analysis. The results show that Tarbiyatul Aulad offers a comprehensive concept of education based on tawhid, moral development, worship habits, and the development of children's intellectual, emotional, and social potential. This concept is still relevant to the needs of modern education that often emphasizes cognitive aspects, but lacks the spiritual and moral dimensions. The application of the principles of Tarbiyatul Aulad can be done through the synergy of family, school, and community in building holistic education based on Islamic values. Thus, this study confirms that Al-Qahthani's thoughts can be used as practical guidelines to strengthen Islamic education amid the challenges of globalization.